Stochastic evolutionary game analysis of food cooperation among countries along the Belt and Road from the perspective of food security - Qinghua, Mao; Linyao, Xu; Qilong, Sun; Mengxin, Guo (Frontiers in Sustainable Food Systems, 2023)
The combination of public health and climate crises has significantly weakened the resilience of the food system in recent years, with the continued spread of New Crown Pneumonia and climate disasters. This paper constructs a three-party stochastic evolutionary game model from the perspective of food security, distinguishes the difference between large and small countries by calculating the cereal selfsufficiency rate, which studies the cooperation strategy with the Belt and Road cereal large countries, cereal small countries and regulatory committees as the object. In addition, we introduce the Gaussian white noise characteristics to characterize the stochastic disturbance of the game system. Then we combine the mathematical derivation of the stochastic evolutionary game analysis with the simulation method, examine the effect of the stochastic disturbance factors on the cooperation, and find out the factors that affect the cooperation. And finally verifies the model and proves the reasonableness and practicability of the model. The results showed that: (1) When the effort level of the large cereal countries reaches the maximum value, the maximum degree of food cooperation is promoted, the willingness of small cereal countries to cooperate and regulatory committees to regulate converged to 1 and remained relatively stable. (2) High incomes in small grain countries promote positive cooperative behavior, but high incomes can lead to instability in the strategic choices of large grain countries and regulatory boards. (3) When the incentive behavior of the regulatory committee reaches the maximum value, it is conducive to the sustainability of the food cooperation system and can avoid the three parties falling into the continuous state of low returns. (4) The uncertainty of external environment affects the decision-making of the tripartite participants.